Reklame som historisk kilde og studiefelt - Myrvang, Christine (Tidsskrift for kulturforskning, 2005)
The article discusses why advertisements rarely are being used as source material in historical research. Although ads have been an important mass cultural verbal and visual expression for more than a century, their status as a historical source is fairly low. By analyzing the front page of a Norwegian newspaper from 1926, the article discusses the more traditional news story in relation to one of the ads on the same page using the analytic tools from historical research: the concept relic (the source as a product of a certain historical situation) versus the concept account (the source as a statement about something that has occurred). The advertisement material tends to blur these borders; the production of the ads has to be seen in relation to the verbal and visual narrative of the ads - as well as ads have a "fuzzy" connection to reality as such. At the same time, the advertisements can be seen as "reality producers" in a broad sense as they are commenting on a wide range of cultural and social issues. Yet, one should be cautious about studying the ads too isolated from other sources, as well as to "over-interpret" them or to ignore who and what the ads themselves disregard.